Metastatic components in colorectal cancer - Javarsiani, Marjan Hajimoradi (J Res Med Sci, 2019)
Recent experiments have shown that cells with different genetic mutations can give rise to cancer transformation, both in vitro and in vivo, supported by the crosstalk between cancer cells and stroma. The stroma and the complex set of involved cells make up the tumor microenvironment that supports the engraftment of metastatic cells. In fact, environmental factors support colorectal cancer arise by formation and maintenance of cancer stem cells (CSCs). In this review, we discuss interactions between CSCs and their microenvironment that can provide better therapeutic opportunities in the metastatic cancer.